Effects of a Heel Wedge in Horses with Superficial Digital Flexor Tendinitis - Clayton, Hilary M.; Willemen, M. A.; Lanovaz, J. L.; Schamhardt, H. C. (Veterinary and Comparative Orthopaedics and Traumatology, 2000)
The objective was to determine whether the use of heel wedges is an appropriate treatment for superficial digital flexor (SDF) tendinitis. The subjects were six warmblood horses in which SDF tendinitis was induced in one forelimb using a collagenase model. The stride characteristics were compared under four conditions: flat shoes; 6° heel wedge following a one hour adaptation; 6° heel wedge following five days adaptation; and one hour after reapplication of flat shoes. Videographic and force data were collected for both forelimbs during the stance phase of the trot, and were combined with morphometric measurements using an inverse dynamics method to calculate net joint moments and joint powers at each of the joints of the forelimbs. Repeated measures ANOVA was used to compare the stride variables across conditions in the lame limb and in the compensating forelimb. Significant kinematic changes in response to the use of heel wedges were confined to the coffin joint which was more flexed due to the more upright orientation of the hoof segment. The onset of breakover was delayed with the hoof wedges. In the compensating limb only, the use of heel wedges was associated with a shift of the net joint moment to the dorsal side of the coffin joint during the first one third of stance. Both forelimbs had significantly smaller peak palmar moments at the coffin joint with heel wedges in the second half of stance, which appeared to be a mechanical consequence of the more flexed position of the coffin joint. Tension was increased in the extensor branches of the suspensory ligament and common digital extensor tendon on the dorsal side, and reduced in the deep digital flexor tendon and its distal accessory ligament on the palmar side. Less energy was absorbed across the coffin joint in both limbs with heel wedges. The study did not reveal changes associated with the use of heel wedges that could be interpreted as a reduction of the effects of lameness due to SDF tendinitis.The objective was to determine whether the application of 60 heel wedges was appropriate for treating horses with superficial digital flexor (SDF) tendinitis. The significant effects of the heel wedges affected the coffin joint and included a more flexed position due to the more upright orientation of the hoof segment, a reduction in the peak palmar moment and less energy absorption across the joint. Since these changes were confined to the coffin joint, they were not interpreted as being beneficial in treating lameness due to SDF tendinitis.
Keywords: Kinematics; kinetics; inverse dynamics; net joint moments; joint powers; farriery